The cultural environment of metaphors: A study of German as a Second/Foreign Language - Evelyn Vovou (Peoples' Friendship University of Russia (RUDN University), 2022)
This paper aims to empirically show that mediation of metaphor in a second language is more than a competence. Metaphor is an ecosystemic construct combining linguistic, cultural and semiotic symbols that may instigate different cognitive functions within the minds of language users in different languages. In order to empirically study the above, a metaphor mediation task was given to Greek speakers of German as a Second Language, where participants had to identify metaphors mediating the content of visual stimuli. The results of the study show that, although the analysed conceptual metaphors proved to be similar between the two languages, the participants could not identify the metaphoric mediation in their second language in more than half the cases. The findings suggest that more parameters should be addressed regarding the mediation of metaphor in a second language, and that triangulation of theories and methodologies is in order for safely analysing an ecosystemic construct such as metaphor.